The Effect of Fasting Blood Glucose (FBG) on Troponin I and Clinical Outcomes in Acute Coronary Syndrome (ACS) : A Retrospective Analysis: A Retrospective Observational Study - Abshori, Nuril Farid; Ahdi, Iwal Reza; Kakiay, Ferdinandus Stevanus (Clinical and Research Journal in Internal Medicine, 2025)
Background: In the early phase of Acute Coronary Syndrome (ACS), simple parameters such as fasting blood glucose (FBG) and cardiac troponin I (cTnI) may provide prognostic information. However, evidence regarding their relationship remains inconsistent, particularly in the Indonesian population. Objective: To investigate the correlation and association between FBG and cTnI in patients with ACS at Karsa Husada Hospital, Batu, Indonesia. Methods: This retrospective observational study included 75 hospitalized ACS patients. Clinical and laboratory data were collected from medical records. Troponin values were log10-transformed. Statistical analyses included Spearman correlation, stepwise linear regression per 10 mg/dL increase in FBG, categorical FBG classification (<100, 100–125, ≥126 mg/dL), trend testing, and restricted cubic spline modeling. Fully adjusted models incorporated age, sex, diabetes, estimated glomerular filtration rate, systolic blood pressure, and heart rate. Results: The median age was 62 years, and 64% were male. FBG showed a weak, non-significant correlation with cTnI (rₛ = 0.19; p = 0.12). After adjustment, each 10 mg/dL increase in FBG was associated with an 8.6% higher cTnI level (β = 0.036; 95% CI −4.5% to +23.6%; p = 0.20). Compared with normal FBG, hyperglycemia (≥126 mg/dL) was associated with a 50.6% higher cTnI level, although this was not statistically significant (p = 0.60), and no significant linear trend was observed (p-trend = 0.55). Spline analysis revealed no significant non-linearity (p = 0.72), and no interaction by diabetes status (p = 0.67). Conclusion: In this ACS population, higher FBG tended to be associated with higher cTnI levels; however, the relationship attenuated and lost significance after adjustment. FBG may serve as an additional risk marker rather than a primary determinant of myocardial injury in the early phase. Keywords: fasting blood glucose, troponin I, acute coronary syndrome, hyperglycemia